Firing patterns of muscle vasoconstrictor neurones in respiratory disease - Macefield, Vaughan G. (Frontiers in Physiology, 2012)
Because the cardiovascular system and respiration are so intimately coupled, disturbances in respiratory control often lead to disturbances in cardiovascular control. Obstructive Sleep Apnoea (OSA), Chronic Obstructive Pulmonary Disease (COPD) and Bronchiectasis (BE) are all associated with a greatly elevated muscle vasoconstrictor drive (muscle sympathetic nerve activity; MSNA). Indeed, the increase in MSNA is comparable to that seen in congestive heart failure (CHF), in which the increase in MSNA compensates for the reduced cardiac output and thereby assists in maintaining blood pressure. However, in OSA – but not COPD or BE – the increase in MSNA can lead to hypertension. Here, the features of the sympathoexcitation in OSA, COPD and BE are reviewed in terms of the firing properties of post-ganglionic muscle vasoconstrictor neurones. Compared to healthy subjects with low levels of resting MSNA, single-unit recordings revealed that the augmented MSNA seen in OSA, BE, COPD and CHF were each associated with an increase in firing probability and mean firing rates of individual neurones. However, unlike patients with heart failure, all patients with respiratory disease exhibited an increase in multiple within-burst firing which, it is argued, reflects an increase in central sympathetic drive. Similar patterns to those seen in OSA, COPD and BE were seen in healthy subjects during an acute increase in muscle vasoconstrictor drive. These observations emphasise the differences by which the sympathetic nervous system grades its output in health and disease, with an increase in firing probability of active neurones and recruitment of additional neurones being the dominant mechanisms.